Low frequency fatigue of quadriceps femoris of handball players during dynamic physical exercise - Lionikas, A.; Skurvydas, A.; Stasiulis, A. (Education. Physical training. Sport, 1998)
The aim of the study was to determine whether the rapid ramp protocol in cycling induces low frequency fatigue (LFF) in quadriceps femoris muscle and if post-tetanic potentiation compensates for it. Handball players 15-16 years of age participated in the experiment (n=12). They had been engaged in regular training for 3-5 years. Maximal voluntary contraction force (MVC) decreased (p<0.05) from 71.1±13 kg to 66.3±5.2 kg after the cycling. The counter squat jump at the same time remained almost unchanged (35.1±5 and 34±6 cm). There was a considerable decrease (p<0.01) in single twitch, 10 and 20 Hz contraction force up to 62±15%, 62±16% and 70.1±12% of the initial respectively. At the same time 50 Hz contraction force consisted of 89±10% (p<0.05) of the initial. It caused the reduction of 20 and 50 Hz contraction force ratio (from 0.72±0.06 to 0.56±0.08) that was considered to be an indicator of LFF. The force-time integral measured in tetanic contractions exhibited profound reduction (p<0.01) at any stimulation frequency employed. In conclusion, the rapid ramp protocol in cycling induced low frequency fatigue (LFF) in quadricep femoris muscle, however, there was no post-tetanic potentiation.